6. EFEKTIVITAS KEBIJAKAN MORATORIUM KAPAL EKS-ASING TERHADAP TINDAK ILLEGAL FISHING DI PERAIRAN INDONESIA PERIODE 2014-2015 - Ingrid Magdalena Sianturi, Sonta Purnama; Putranti, Ika Riswanti; Pattipelohy, Shary Charlotte (Journal of International Relations, 2016)
Illegal fishing activities in Indonesia are on the increase and bring harm to the country inmany aspects such as economy, environment, social welfare, until the country'ssovereignty. Therefore, Indonesia has made many regulations related to illegal fishing, butdue to the frequent occurrence of the illegal fishing in Indonesian waters, Minister ofMaritime Affairs and Fisheries of the Republic of Indonesia Susi Pudjiastuti, implementsmoratorium ex-foreign vessels policy as President Joko Widodo wants Indonesia tobecome the pivot of the world maritime. Moratorium of ex-foreign vessels is a dismissal oftemporary permittion for vessels above 30 GT that manufactured abroad. The purpose ofthe permits dismissal of sailing and operate in Indonesian waters are because there are asuspicion of foreign vessels is an ex-offender of illegal fishing and get permission illegallyto sail and operate that detriment Indonesia. This research aims to determine the policy ofmoratorium ex-foreign vessels set by the Indonesian’s government in dealing with cases ofillegal fishing is effective or not during the runs of the moratorium from 2014-2015. Thetheoritical framework used in this research are illegal fishing, the concept of supply chainmanagement, and concept of national interest. This type of research is an explanatory withqualitative data analysis techniques through data collecting techniques by literature andinterviews. Results of this research is to describe the effectiveness of the moratorium exforeignvessels in countering illegal fishing in Indonesian waters. Effectiveness researchindicators used are the number of illegal fishing acts in Indonesia at the time of themoratorium runs, the impact of the moratorium, the moratorium policy’s infrastructure, theapplication of the concept of supply chain management to the research objects, and thesatisfaction levels of the government on the results of ex-foreign vessels moratorium.